Reliious tourism at Pedra de Santo Antônio in Fagundes-PB: reflections on social and environmental impacts (Research, Society and Development, 2021)
This article discusses the importance of religious tourism as one of the main segments that has been continuously developed since the beginning of the development of tourism practices. Thus, this article aims to highlight and analyze the practice of religious tourism in Pedra de Santo Antônio and highlight the economic movement that this activity can provide for the municipality of Fagundes-PB, in addition to highlighting the environmental problems arising from tourism. The methodology applied in the study comprises a case study and a literature review, addressing tourist aspects of the city of Fagundes with an emphasis on the economic development of the city. The results obtained from the research highlight the great tourist potential of the city when related to religious tourism, however there is still a lack of government investments for local tourism to develop, generating more jobs for the local population. Another point that draws attention is the municipality's structural unpreparedness to receive tourists, as the city does not offer accommodation for tourists and visitors looking for Pedra de Santo Antônio. It is concluded that, for the city to develop as a touristic environment, investments in the structure are necessary, in addition to becoming more cozy, since many people when they are not welcomed (installed) do not return to the tourist spot or refer people nearby.